The Impact of Marketing Capability and Customer Value Creation on Iconic Product Advantages and Marketing Performance in SMEs - Aris Mardiyono; Gita Sugiyarti (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study examines the impact of product selling power and customer value creation on the benefits and marketing performance of iconic products among SMEs. This study uses a quantitative research method with a survey approach to test the relationship between variables objectively and measurably. The study was conducted in Semarang Regency from June to September 2024. The research sample consisted of 220 local wisdom-based SMEs, especially batik, water hyacinth, and clay craft SMEs. Sampling was carried out using a purposive sampling method. Data collection was carried out using a questionnaire with a 7-point Likert scale, then analyzed using Structural Equation Modeling (SEM) with the help of AMOS software. The results confirm that marketing capabilities significantly increase iconic product excellence and marketing performance. In addition, customer value creation has a strong impact on iconic product excellence and marketing performance. This study also found that iconic product excellence mediates the relationship between marketing capabilities, customer value creation, and marketing performance. These findings highlight the importance of customer-centric strategies and brand differentiation for SMEs.